Community Perceptions of the Role of Nurses as Health Service Providers - Mutmainnah Mutmainnah; Fathimah Kelrey; Endri Mustofa; Rita Kombong; Ireine Tauran (Indonesian Journal of Global Health Research, 2021)
Nurses are medical officers in hospitals who have an important role in monitoring patient conditions, being involved in planning patient care, and providing interventions in disease management. Current conditions, the role of public health nurses has not been implemented in its entirety. The aim of this research is to analyze public perceptions of the role of nurses as providers of health services. This research was carried out at the Segeri Health Center, Kel. Segeri Kec. Segeri Kab. Pangkep with purposive sampling. The instrument used in this research was a questionnaire regarding public perceptions of the role of nurses which includes the role of nurses as service providers, educators/counselors, case finders, role models/role models, coordinators/collaborators. Univariate data analysis was carried out with the aim of explaining or describing the characteristics of each variable. The research results show that there are good perceptions of respondents regarding the role of nurses, which includes the role of nurses as service providers, educators/counselors, case finders, role models/role models, coordinators/collaborators.